Meniscectomy and Resultant Articular Cartilage Lesions of the Knee Among Prospective National Football League Players: An Imaging and Performance Analysis. Issue 1 (January 2018) - Chahla, Jorge; Cinque, Mark E.; Godin, Jonathan A.; Sanchez, George; Lebus, George F.; Whalen, James M.; Price, Mark D.; Kennedy, Nicholas I.; Moatshe, Gilbert; LaPrade, Robert F.; Provencher, Matthew T.
Background: The effect of prior meniscectomy and the resulting reduction in meniscal tissue on a potential National Football League (NFL) player's articular cartilage status and performance remain poorly elucidated. Purpose/Hypothesis: (1) To determine the epidemiology, imaging characteristics, and associated articular cartilage pathology of the knee among players with a previous meniscectomy who were participating in the NFL Combine and (2) to evaluate the effect of these injuries on performance as compared with matched controls. The hypothesis was that players with less meniscal tissue would have worse cartilage status and inferior performance metrics in their first 2 NFL seasons. Study Design: Cohort study; Level of evidence, 3. Methods: All athletes with a history of a meniscectomy and magnetic resonance imaging scan of the knee who participated in the NFL Combine (2009-2015) were identified. Medical records and imaging were analyzed, and surgical history, games missed in college, position played, and draft position were documented. The conditions of the meniscus and cartilage were graded with modified ISAKOS scores (International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine) and ICRS scores (International Cartilage Repair Society), respectively. Players with a previous meniscectomy of at least 10% of total medial or lateral meniscal volume excised (ISAKOS meniscus grade ≤8) and matched controls without a significant pre-Combine injury were similarly evaluated and compared by position of play through analysis of draft position, number of games played and started, and how many eligible plays they participated in (snap percentage) within the first 2 NFL seasons. Results: Of the 2285 players who participated in the NFL Combine (2009-2015), 287 players (322 knees) had a prior meniscectomy (206 lateral, 81 medial). Among these players, 247 (85%) had a total of 249 chondral lesions, most commonly on the lateral femoral condyle (111 lesions, 45%). There was a significant inverse correlation found between the ISAKOS medial and lateral meniscus grade and the corresponding compartment chondral lesion grade ( P = .001). A poorer meniscus score was also associated with worse chondral pathology, especially in the lateral compartment. After controlling for position of play, the injury-free control group had a significantly greater number of total games played and games started and higher snap percentage versus those with a prior meniscectomy of at least 10% volume (ISAKOS meniscus grade ≤8). Players with severe chondral lesions (ICRS grade 4) in the medial and lateral compartments had significantly worse performance metrics when compared with matched controls. Conclusion: Previous meniscectomy of at least 10% of total medial or lateral meniscus volume in prospective NFL players was significantly correlated with larger and more severe chondral lesions. Chondral and meniscal defects of the knee were found to result in a significant decrease in objective performance measures during a player's initial NFL career versus matched controls. Given these findings, players with a prior meniscectomy with evidence of chondral damage should be evaluated carefully for their overall functional levels; however, additional work is needed to fully clarify the effect of prior knee meniscal surgery on overall NFL performance.